DIGITAL SIGNATURE :BEST PRACTICE SOLUTION FOR THE DISTRIBUTION OF LETTERS IN COLLEGE - Untung Rahardja; Muhamad Yusup; Ari Asmawati (CCIT Journal, 2013)
Purpose of implementation ofweb-based information systems that allow user stoaccess information anywhere and anytime. Especiallyin making letters out stillusea wet signature. So that has not been able to provide information quickly and accurately. Identified there are7 (seven) point concerns the handling and processing of the paperstoday. However, the problem can besolved by building a Digital Signature Designand is online, so it can reduce the error rate and the information obtainedis really precise, accurate and in accordance with the needs. Obviously with the directional flow methodology description, ranging from th eillustration Figure Digital Signature, Flow distribution sub part Digital Signature, Digital Signature Flowchart, cycle and Digital Signature Digital Signature Use Case. From the Literature Review,has been much research on the Digital Signature Algorithm and Digital Signature Scheme. In the implementation phaseof the prototype described in detail the design of Digital Signature, the program listings are shown to display a letter that has been approved and has been signed. It can be also generatedauthentication system called digital signature is a waytoen sure the authenticity of an electronic document and keep documents in a time sender can not deny that she has sent the document.